2011
DOI: 10.3382/ps.2010-01296
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an indigenous source of rock phosphate as a supplement for broiler chickens

Abstract: This study investigated the effects of replacing dicalcium phosphate (DCP) with Hazara rock phosphate (HRP) on the growth performance of broiler chickens. The purpose was to determine the maximum level of F that could be well tolerated. The HRP (13.16% P and 2.98% F) was incorporated into a standard corn- and soybean meal-based diet by replacing 0, 25, 50, 75, and 100% of DCP based on P. Each treatment consisted of 5 replicate pens of 10 chicks each. The Ca and nonphytate P contents of all diets were maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…), the leukocyte count increases [41]. In general, lower P availability or imbalance in the Ca to P ratio might be stressful to the broilers, which could lead to a change in leukocyte counts [35,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), the leukocyte count increases [41]. In general, lower P availability or imbalance in the Ca to P ratio might be stressful to the broilers, which could lead to a change in leukocyte counts [35,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The tibia and serum analysis results elucidated a normal level of P utilization. Previous research showed that the source of P supplement had a significant effect on the Ca and P contents of tibia and blood serum [35]. This difference may have resulted from the imbalance in the Ca to P ratio due to lower phosphate availability.…”
Section: Discussionmentioning
confidence: 99%